PENGGUNAAN BATU CERMAT DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KREATIF DAN BUDAYA LITERASI SISWA - Abdul Hakim (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
Based on the data and experience of researchers in classes that are able to show interest in literacy and critical thinking skills is still low. Therefore, researchers applied the Batu Cermat method. Batu Cermat comes from “baca-tulis-uji-cerpen-matematika,” (read-write-test-short story mathematics). Batu Cermat aims to civilize literacy and instill communication skills, collaborate, think critically, and creatively with students. This article is in the form of qualitative research, the best practice of researchers applying Batu Cermat to students of SMPN 1 Dolopo starting the 2015/216 school year to 2017/2018. The information needed is obtained by the documentation study technique, in the form of using a list of values ​​supported by a questionnaire. Through Batu Cermat, students are given the opportunity to think creatively by making short stories in mathematics. How, with m ema be incorporated math problems or related information in a short story, and be able to solve the problem themselves. The validity is tested its validity with each other carefully and resolved. As a result, students are able to make short, good mathematical nuances of short story work according to the rules of short story writing. Proven Batu Cermat can be a catalyst in civilizing literacy and developing the ability to think creatively students. The Batu Cermat is more optimal, if the reading movement becomes more entrenched and requires patience and cooperation across subjects. Up to now, the students' careful work has published four ISBN short story mathematics books.